Manajemen Program Kesiswaan Dalam Meningkatkan Mutu Lulusan Madrasah - Hilma Hanafiyah; Umar Sidiq (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah dan Ilmu Keguruan, IAIN Ponorogo, 2023)
Education is the norm and provision for life in society, nation and state. In the life of a state, the quality of a nation will be determined by the quality of its human resources. Indirectly, education has positive implications for the survival of a nation and the state of a country in the future cannot escape the influence of the implementation of education. However, in reality, the quality of education in Indonesia is currently very concerning. This is due to the existence of several problems in the Indonesian education system that result in the low quality of education in Indonesia. From the various problems in the quality and quality of Indonesian education above, the implementation of student management as an effort to improve the quality of education and the quality of graduates is one of the solutions that can be done. The implementation of student management is expected to improve the quality and quality of education, so that later educational institutions can produce quality students.